THE RELATIONSHIP BETWEEN SYMBOL AND MEANING IN THE FILM ZOOTOPIA - Dwi Lestari Septiani; Sari Rejeki; Ni Made Widisanti S (Journal Albion : Journal of English Literature, Language, and Culture, 2019)
ABSTRACTThis research discusses the relationship between the symbol and meaning in Zootopia, a film by Jared Bush and Phil Johnston. The objectives of this research is to show the types of symbol in Zootopia and its meaning by identifying the types of symbol and its meaning based on the speakers utterance and the context of the utterance itself. The method used in this research is descriptive analysis with library research technique. The results of this research shows that there are 15 symbols in this movie. From 15 symbols mentioned, all the symbols in Zootopia are private symbol. The meaning of symbol are determined by its reference, which refers to the words and sentences, and also by supportive context which explains the reference. Symbols and meanings in this movie are closely related and become a unity that builds storylines and characters. The symbols in this movie are intentionally used to help in conveying the content and message of the movie. Keywords: Symbol, meaning, movie.